Utilization of Solar Power Plant in Indonesia: A Review - Hardianto, Hardianto (International Journal of Environment, Engineering & Education, 2019)
Energy currently has a crucial role in human life. So far, the primary buffer of energy needs still relies on petroleum. Meanwhile, petroleum is inevitably increasingly scarce and expensive. With the state of the depletion of fossil energy sources, in today's world, there is a shift from the use of non-renewable energy sources to renewable energy sources. Of the many renewable energy sources, the use of energy through solar cells is the most potent alternative to applied in Indonesia. Solar energy is one of the energies currently actively developed by the Indonesian government because as a tropical country, Indonesia has considerable solar energy potential. Solar energy is extraordinary because it is not a pollutant, cannot use up, can trust and does not buy. There are many ways to harness energy from the sun. The electricity we can use today is electricity produced from the process of burning fossil fuels such as coal, oil or natural gas. The combustion results will produce carbon dioxide gas which can damage or adversely affect the environment. Solar electricity can provide electricity continuously because its energy source is a renewable energy source and is also a clean and environmentally friendly energy, to reduce greenhouse gas emissions. Besides, solar electricity can provide electricity quickly and does not require individual costs for maintenance and can provide electricity needs in rural areas, isolated areas, and islands that not electrified by the government.